PERTUMBUHAN DAN PRODUKSI PIGMEN MERAH OLEH Serratia marcescens PADA BERBAGAI SUMBER KARBON - Setiawan Wicaksono; Endang Kusdiyantini; Budi Raharjo (Jurnal Akademika Biologi, 2017)
Serratia marcescens is one of the red pigment producing bacteria which is widely used as natural dye. This bacterium was isolated from the sediment of hot springs in Gedong Songo, Bandungan, Semarang. S. marcescens has potential as a natural pigment producer. This study was conducted to measure the growth and production of pigments in NB medium containing different carbon sources. The sources of carbon used were glucose, fructose, maltose, and lactose. The method used were growth measurement based on dry weight value of cell and value of ODλ=600nm, measurement of reducing sugar, measurement of the acidity of the growth medium, and measurement of red pigment concentration. The results obtained in this study indicated that the provision of carbon sources has no significant effect on the growth of S. marcescens. The best carbon source for red pigment production is lactose with pigment concentration of 0.451 mg/L achieved at 24 hours incubation time.Keywords: Serratia marcescens, Growth, Carbon Source, Red Pigment.